2008
DOI: 10.1111/j.1752-248x.2008.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell granuloma in the oral cavity

Abstract: Plasma cells are terminally differentiated B lymphocytes which are typically found in the red pulp of the spleen, medulla of the lymph nodes, tonsils, lamina propria of the entire gastrointestinal tract, mucosa of the nose and upper airway, and sites of inflammation. They are characterised by basophilic cytoplasm with an eccentrically placed nucleus. They range in size from 14 to 20 µm. A plasma cell's main function is to produce immunoglobulins or antibodies. Plasma cell granuloma is a plasma cell lesion whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Plasma cell infiltrates have also been found on the vulva, buccal mucosa, palate, nasal aperture, gingiva, lips, tongue, epiglottis, larynx and other orificial surfaces [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma cell infiltrates have also been found on the vulva, buccal mucosa, palate, nasal aperture, gingiva, lips, tongue, epiglottis, larynx and other orificial surfaces [1].…”
Section: Discussionmentioning
confidence: 99%
“…They range in size from 14 to 20 lm. A plasma cell's main function is to produce immunoglobulins or antibodies [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been suggested that it represents the inflammation following minor trauma or surgery, or to be associated with other malignancy. [2] In present case, history of placement of quid in labial vestibule can be sorted as chronic trauma leading to inflammation, though the absolute link cannot be established. Not only this, an autoimmune mechanism has also been implicated in the pathogenesis of plasma cell granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…However, various hypothesis have suggested that the pathogenesis has infectious, autoimmune and vascular origin.In some cases, it is thought to result from inflammation following minor trauma or surgery, or to be associated with other malignancy. [2] The term "plasma cell granuloma" was coined by Bahadori and Liebow in 1973 to describe a pseudotumor lesion of lung. [3] This rare lesion is commonly seen in the lungs and some other anatomic locations such as brain, kidney, stomach, heart.…”
Section: Introductionmentioning
confidence: 99%